Support of adult urinary incontinence products: recommendations to assure safety and regulatory compliance through application of a risk assessment framework - Krause, Edburga L.; Hattersley, Anne M.; Abbinante-Nissen, Joan M.; Gutshall, Denise; Woeller, Kara E. (Frontiers in Reproductive Health, 2023)
Urinary incontinence (UI) or involuntary loss of urine is a common chronic medical condition among women. It is estimated that 5%−70% of the population experiences incontinence with most studies suggesting 25%−45% of the population. Varying definitions of UI (e.g., stress, urgency, mixed) exist, and inconsistent symptom assessment tools, age, and gender can affect the estimate of incidence. Disposable Adult Incontinence products were first introduced into the market in the late 1970s and initially were used mostly in nursing homes and hospitals. However, during the 1980s, the market for incontinence products via retail outlets dramatically increased as awareness of the benefits of the products grew and stigma about their use declined. Today's products that manage urine loss have an extensive history and have evolved with time. Always products were introduced into the market in 2014 and are designed to meet the needs of women of all ages. Considered medical devices in some countries, regional regulations and global guidelines require clear planning, thorough assessment, and concise documentation of clinical safety. This manuscript will briefly review the regulatory landscape with a specific focus on European Union regulations. As previously published, the iterative, risk assessment framework used to assess the safety of Always incontinence products confirms that these products are compatible with skin and can be used safely. This manuscript will expand on the current literature highlighting additional steps that help assure the safety and compliance of the products from quality assurance programs through comprehensive post-market safety surveillance. Recommendations to help ensure several of the key regulatory requirements are met are outlined in the context of a risk assessment framework used to assure safety.